Breaking dawn - Meyer, Stephenie (New York : Little, Brown and Company, 2008)
Pulled in one direction by her intense passion for vampire Edward Cullen, and in another by her profound connection with werewolf Jacob Black, Bella Swan has endured a tumultuous year of temptation, loss, and strife to reach the ultimate turning point. She must choose to either join the dark but seductive world of immortals or pursue a fully human life.
Keywords: Vampires -- Fiction; Fantasy fiction